(untitled) (Prilozi za orijentalnu filologiju, 2017)
This paper makes public a document from the Archives of the Presidency of the Government of the Turkish Republic (the collection “Mühimme defteri”, Book No. 5, p. 196). The document dates from 1564 and refers to the recruitment of boys for adžemi oglani, the so-called blood-tribute, or devširme. According to Ottoman law the devširme, which existed for about two and a half centuries (from the first half of the fifteenth to the second half of the seventeenth centuries) was at first levied only in the European part of the Empire, but later it was done also in its Asian part. In the beginning only boys from non-Muslim population were taken but later boys from Muslim population were taken as well. The recruitment was done in time spans of from three to seven years. Recruited were only healthy and handsome boys from 8 to 18, rarely to 20 years of age. Exempted from recruitment were the only sons, boys who were learning some trade, married persons or those who had some physical or mental deficiency. Approximately forty households gave one boy. There were strict rules regarding the devširme and very severe punishments in cases of their violation: The document which we publish here speaks about the recruitment of only Muslim boys for adžemi oglan. It shows clearly that as early as the second half of the fifteenth century in the region of Bosnia and at the request of the Bosnians themselves boys were taken for adžemi oglan “whether they .be circumcised or not”, i. e. whether they were of Muslim or non-Muslim origin. The document of 1564 presented here indicates thus a certain evolution of the rules regarding the devširme, at least in the cases of the Bosnian, Herzegovinian, and Klis sangaks. This document which is in fact an order (hüküm) of the central government sent to the administrative and judiciary bodies of the three above-mentioned sangaks, demands explicitly that exclusively boys from the Muslim part of the population of these regions be taken for adžemi oglan. The order particularly emphasizes that the tribute should be taken from those segments of the population which lived there since ancient times, and by no means the boys born or by origin from other regions who happened to be on the territory of these three sangaks.